A comparative study on the effect of different cooling media on the keeping quality of fish sausage. - Esporlas, Amelia E. (College of Fisheries, University of the Philippines, 1978)
Fish sausage samples prepared from shark meat was stored separately in ice cubes (32 degrees F), chiller (39 degrees F), freezer (26 degrees F) and dry ice (-40 degrees F). Some samples were kept at room temperature and analyzed for changes in keeping quality and acceptability in the same manner of treatment as those in the different cooling media. Storage analyses of the lots were terminated when the samples reached a state of quality rejection as judge by the taste panel. Analysis of the samples was done by organoleptic. The lots stored in different cooling media showed different types of changes, some of which led to rejection. The liquefaction observed in chilled samples may have caused a change in flavor, which made it significantly different from the other lots at 1% level of probability and which was rejected the earliest. The formation of black spots accompanying discoloration was also evident and was suspected to have been an outcome of bacterial action and formation of peroxides. Liquefaction observed in iced samples assumed to be caused by water from melting ice entering thru the casing has, in a way, lowered down the texture scores during evaluation. Coarseness in texture was exhibited by samples in the freezer brought about by large crystals formed during storage. The control samples at room temperature showed gas formation and a decrease in pH, which may indicate starch fermentation possibly by lactic acid bacteria. Highest scores in general acceptability tests was given to samples stored in dry ice (-40 degrees F) since no visible changes in texture, color, and flavor were noted up to the seventh week of storage.